Regulation of the Muscarinic M3 Receptor by Myocardin-Related Transcription Factors - Liu, Li; Rippe, Catarina; Hansson, Ola; Kryvokhyzha, Dmytro; Fisher, Steven; Ekman, Mari; Swärd, Karl (Frontiers in Physiology, 2021)
Myocardin related transcription factors (MRTFs: myocardin/MYOCD, MRTF-A/MRTFA, and MRTF-B/MRTFB) are co-factors of serum response factor (SRF) that activate the smooth muscle cell (SMC) gene program, and that play roles in cardiovascular development and mechanobiology. Gain and loss of function experiments have defined the SMC gene program under control of MRTFs, yet full understanding of their impact is lacking. In the present study, we tested the hypothesis that the muscarinic M3 receptor (CHRM3) is regulated by MRTFs together with serum response factor (SRF). Forced expression of MYOCD (8d) in human coronary artery smooth muscle cells followed by RNA-sequencing showed increased levels of M2, M3 and M5 receptors (CHRM2: 2-fold, CHRM3: 16-fold, and CHRM5: 2-fold). The effect of MYOCD on M3 was confirmed by RT-qPCR using both coronary artery and urinary bladder SMCs, and correlation analyses using human transcriptomic datasets suggested that M3 may also be regulated by MRTF-B. Head-to-head comparisons of MYOCD, MRTF-A and MRTF-B, argued that while all MRTFs are effective, MRTF-B is the most powerful transactivator of CHRM3, causing a 600-fold increase at 120h. Accordingly, MRTF-B conferred responsiveness to the muscarinic agonist carbachol in Ca2+ imaging experiments. M3 was suppressed on treatment with the MRTF-SRF inhibitor CCG-1423 using SMCs transduced with either MRTF-A or MRTF-B and using intact mouse esophagus in culture (by 92±2%). Moreover, silencing of SRF with a short hairpin reduced CHRM3 (by >60%) in parallel with α-actin (ACTA2). Tamoxifen inducible knockout of Srf in smooth muscle reduced Srf (by 54±4%) and Chrm3 (by 41±6%) in the urinary bladder at 10 days, but Srf was much less reduced or unchanged in aorta, ileum, colon, trachea, and esophagus. Longer induction (21d) further accentuated the reduction of Chrm3 in the bladder and ileum, but no change was seen in the aorta. Single cell RNA-sequencing revealed that Mrtfb dominates in ECs, while Myocd dominates in SMCs, raising the possibility that Chrm3 may be driven by Mrtfb-Srf in the endothelium and by Myocd-Srf in SMCs. These findings define a novel transcriptional control mechanism for muscarinic M3 receptors in human cells, and in mice, that could be targeted for therapy.